Research Report: Exhibiting Gender: Exploring the Dynamic Relationships between Fashion, Gender, and Mannequins in Museum Display. (2nd January 2019) - Chapin, Chloe; Green, Denise Nicole; Neuberg, Samuel
Abstract : Social and cultural understandings of gender have shifted dramatically in recent years. Arguably, an increasing awareness of the fluidity and performativity of gender has allowed for recognition of identities and expressions that complicate the male/female binary. Fashion, habitus, and manipulation of the human body are critical to the visible, tangible production of gender. In our research, we explore how fashion and costume museums are engaging with this shift77 and, more specifically, with the representation of bodies through the use of mannequins in museum exhibition spaces. We begin with historical and contemporary context of the current "Gender Revolution" and report on findings from a survey of museum professionals within our field who regularly work with mannequins for display of their dress collections.